2010
DOI: 10.1158/0008-5472.can-10-1100
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of the Ubiquitin Protease UBP43 Destabilizes Transcription Factor PML/RARα and Inhibits the Growth of Acute Promyelocytic Leukemia

Abstract: More effective treatments for acute promyelocytic leukemia (APL) are needed. APL cell treatment with all-trans-retinoic acid (RA) degrades the chimeric, dominant-negative-acting transcription factor promyelocytic leukemia gene (PML)/RARa, which is generated in APL by chromosomal translocation. The E1-like ubiquitinactivating enzyme (UBE1L) associates with interferon-stimulated gene ISG15 that binds and represses PML/ RARa protein. Ubiquitin protease UBP43/USP18 removes ISG15 from conjugated proteins. In this s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 40 publications
5
78
0
Order By: Relevance
“…Both ISG15 [36] and USP18 [19] are deregulated in different cancers, consistent with an important functional role for this DUB in homeostasis of growth-regulatory proteins. This view is supported by our prior work that established ISGylation affects stability of key growth-regulatory proteins in acute promyelocytic leukemia (APL) and lung cancer [16, 17, 19, 20]. Improved understanding of the functional roles played by ISGylation should advance our knowledge of protein destabilization pathways that control oncogenesis by precisely regulating intracellular oncoprotein or tumor suppressor proteins.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Both ISG15 [36] and USP18 [19] are deregulated in different cancers, consistent with an important functional role for this DUB in homeostasis of growth-regulatory proteins. This view is supported by our prior work that established ISGylation affects stability of key growth-regulatory proteins in acute promyelocytic leukemia (APL) and lung cancer [16, 17, 19, 20]. Improved understanding of the functional roles played by ISGylation should advance our knowledge of protein destabilization pathways that control oncogenesis by precisely regulating intracellular oncoprotein or tumor suppressor proteins.…”
Section: Discussionmentioning
confidence: 82%
“…The major deubiquitinating enzyme ubiquitin specific peptidase 18 (USP18) can remove ISG15 from its target proteins, reversing effects of ISGylation [15]. Studies showed that ISGylation results in destabilization of specific protein substrates [1620]. The precise consequences of ISGylation are being elucidated, but there is growing evidence that this pathway has specialized functions [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical investigations revealed that atRA induces terminal differentiation in the leukemic cells by promoting the degradation of the fusion protein through the action of the UBE1L ubiquitin-activating enzyme [56]. Recent studies identified the ubiquitin-specific protease UBP43, an antagonist of UBE1L, as an antineoplastic target whose inhibition destabilizes the t(15;17) PML/RARα fusion protein and induces apoptosis of APL cells [57]. The causative role of a single molecular defect paved the way for differentiation-based therapy and led to successful clinical application of atRA and 13- cis -RA for the treatment of APL (Table 2) [58].…”
Section: Medical Use Of Retinoids and Rexinoidsmentioning
confidence: 99%
“…[14][15][16][17][18] Purification and identification of Fas-associated proteins BJAB cells were screened for potential binding modulators of Fas as described in supplemental Methods.…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%